2015
DOI: 10.2465/jmps.141020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clinopyroxene composition on Fe–Mg distribution coefficient between garnet and clinopyroxene

Abstract: This study examines the effect of jadeite content (Xjd) in omphacite on Fe-Mg distribution coefficient between garnet and clinopyroxene (K D ) by using natural data obtained from ultrahigh-pressure eclogites of the Sulu region, China. A previous study has already pointed out that a negative correlation between lnK D and Xjd and a positive correlation between Fe# [= Fe 2+ /(Fe 2+ + Mg)] of omphacite and Xjd are present. On the other hand, this study newly recognized that K D decreases with decreasing Ca + Na + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…12). Similar positive correlations between X jd and Fe 2+ /(Fe 2+ + Mg) have been noted for other UHP eclogites from the Sulu region (Hirajima, 1996;Nakamura et al, 2015). There is no distinct compositional difference in omphacite among the rock types in Qinglongshan (Fig.…”
Section: Omphacitesupporting
confidence: 78%
See 1 more Smart Citation
“…12). Similar positive correlations between X jd and Fe 2+ /(Fe 2+ + Mg) have been noted for other UHP eclogites from the Sulu region (Hirajima, 1996;Nakamura et al, 2015). There is no distinct compositional difference in omphacite among the rock types in Qinglongshan (Fig.…”
Section: Omphacitesupporting
confidence: 78%
“…This positive correlation is consistent with that reported by Hirajima (1996) in the Yangkou area of the Sulu region, but such a correlation is not necessarily because of the non-ideality of the clinopyroxene solid-solution. Nakamura et al (2015) noted that the use of omphacite with Ca + Na + K contents less than 1.00 a.p.f.u. provides excessively high temperatures.…”
Section: Pressure-temperature Estimationmentioning
confidence: 99%
“…Nakamura et al . () suggested that both high Mg–Fe pyroxene and jadeite components of sodic pyroxene give overestimates of Grt–Cpx geothermometry. The higher temperature for 91ZY05b might thus be attributed to the effect of the high jadeite composition.…”
Section: Discussionmentioning
confidence: 97%
“…An omphacite in sample 91ZY05b, which gave a distinctly higher temperature of 830°C, is significantly richer in jadeite (Jd 53 ) than that in other samples (Enami & Nagasaki, 1999). Nakamura et al (2015) suggested that both high Mg-Fe pyroxene and jadeite components of sodic pyroxene give overestimates of Grt-Cpx geothermometry. The higher temperature for 91ZY05b might thus be attributed to the effect of the high jadeite composition.…”
Section: Comparison With Previous Studies Of Peak P-t Estimatesmentioning
confidence: 99%
“…In addition, samples ND141 and ND142-1 display wide-ranging P-T conditions of 3.2-4.8 GPa and 960-1160 °C and 3.3-4.6 GPa and 920-1100 °C, respectively. These varied P-T conditions may be due to potential uncertainties of the geotheromobarometers, such as effect of clinopyroxene composition on the Fe-Mg distribution coefficient suggested by Hirajima (1996) and Nakamura et al (2015). Although sample ND128c shows relatively low-P-T conditions, the P-T conditions of the Ky-bearing samples collected from the northern and southeastern parts of the block are fairly consistent between the two localities.…”
Section: Estimations Of P-tmentioning
confidence: 92%